Amyloid- and FDG-PET in sporadic Creutzfeldt-Jakob disease: Correlation with pathological prion protein in neuropathology. Issue 3 (4th May 2017) - Matías-Guiu, Jordi A.; Guerrero-Márquez, Carmen; Cabrera-Martín, María Nieves; Gómez-Pinedo, Ulises; Romeral, María; Mayo, Diego; Porta-Etessam, Jesús; Moreno-Ramos, Teresa; Carreras, José Luis; Matías-Guiu, Jorge
ABSTRACT: Introduction. The role of positron emission tomography (PET) in Creutzfeldt-Jakob disease is less defined than in other neurodegenerative diseases. We studied the correlation between the uptake of 18 F-florbetaben and 18 F-fluorodeoxyglucose with pathological prion protein deposition in histopathology in a case.Methods. A patient with 80 y old with a rapid neurological deterioration with a confirmed diagnosis of CJD was studied. PET and MRI studies were performed between 13–20 d before the death. A region of interest analysis was performed using Statistical Parametric Mapping.Results. MRI showed atrophy with no other alterations. FDG-PET showed extensive areas of hypometabolism including left frontoparietal lobes as well as bilateral thalamus. Correlation between uptake of 18 F-florbetaben and pathological prion protein deposition was r = 0.786 (p < 0.05). Otherwise, correlation between uptake of 18 F-FDG and pathological prion protein was r = 0.357 (p = 0.385). Immunohistochemistry with β-amyloid did not show amyloid deposition or neuritic plaques.Conclusions. Our study supports the use of FDG-PET in the assessment of CJD. FDG-PET may be especially useful in cases of suspected CJD and negative MRI. Furthermore, this case report provides more evidence about the behavioral of amyloid tracers, and the possibility of a low-affinity binding to other non-amyloid proteins, such as the pathological prion protein, is discussed.